The novel and the myth of the epic: Balestrini, Lukács, and the cathartic experience. (November 2020) - Castaldo, Achille
In this article, I address the critical reception of Nanni Balestrini's narrative work, focusing in particular on the novel Vogliamo tutto (1971). I compare the interpretative model, which sees this text as overcoming the novelistic form and moving toward the epic, with a similar model in György Lukács' foundational text The Theory of the Novel (1916), which sets up an opposition between the novel, understood as an expression of the irrelevance of private existence in our society, and the idea of a "rebirth" of the epic as a redemptive collective dimension. In order to investigate the textual mechanisms that generate a reading experience that has been defined resorting to the cliché of the epic, I draw on Lukács' later Aesthetics (1962). In this work, he offers a response to the impasses of his earlier thought by using the concept of catharsis, which explains the effects of a work of art on the reader/viewer through the pathetic energy generated by the dissolution of the subjective perspective. Through a close reading of key passages from Vogliamo tutto, I show how the rhetorical structure of the text is grounded in a repeated dissolution of the narrative point of view (the narrator's voice) in the collective voice of the workers. I argue that the "pathetic intensity" produced by this loss of subjectivity inscribes the communal existence of the political struggles of the time in the immediacy of the reading experience.